Alox15/15-HpETE Aggravates Myocardial Ischemia-Reperfusion Injury by Promoting Cardiomyocyte Ferroptosis - Cai, Wenbin; Liu, Le; Shi, Xuelian; Liu, Yanan; Wang, Jin; Fang, Xuan; Chen, Zhipeng; Ai, Ding; Zhu, Yi; Zhang, Xu (Circulation (New York, N.Y.), 2023)
Myocardial ischemia-reperfusion (I/R) injury causes cardiac dysfunction to myocardial cell loss and fibrosis. Prevention of cell death is important to protect cardiac function after I/R injury. The process of reperfusion can lead to multiple types of cardiomyocyte death, including necrosis, apoptosis, autophagy, and ferroptosis. However, the time point at which the various modes of cell death occur after reperfusion injury and the mechanisms underlying ferroptosis regulation in cardiomyocytes are still unclear. Using a left anterior descending coronary artery ligation mouse model, we sought to investigate the time point at which the various modes of cell death occur after reperfusion injury. To discover the key molecules involved in cardiomyocyte ferroptosis, we performed a metabolomics study. Loss/gain-of-function approaches were used to understand the role of 15-lipoxygenase (Alox15) and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (Pgc1α) in myocardial I/R injury. We found that apoptosis and necrosis occurred in the early phase of I/R injury, and that ferroptosis was the predominant form of cell death during the prolonged reperfusion. Metabolomic profiling of eicosanoids revealed that Alox15 metabolites accumulated in ferroptotic cardiomyocytes. We demonstrated that Alox15 expression was specifically increased in the injured area of the left ventricle below the suture and colocalized with cardiomyocytes. Furthermore, myocardial-specific knockout of Alox15 in mice alleviated I/R injury and restored cardiac function. 15-Hydroperoxyeicosatetraenoic acid (15-HpETE), an intermediate metabolite derived from arachidonic acid by Alox15, was identified as a trigger for cardiomyocyte ferroptosis. We explored the mechanism underlying its effects and found that 15-HpETE promoted the binding of Pgc1α to the ubiquitin ligase ring finger protein 34, leading to its ubiquitin-dependent degradation. Consequently, attenuated mitochondrial biogenesis and abnormal mitochondrial morphology were observed. ML351, a specific inhibitor of Alox15, increased the protein level of Pgc1α, inhibited cardiomyocyte ferroptosis, protected the injured myocardium, and caused cardiac function recovery. Together, our results established that Alox15/15-HpETE-mediated cardiomyocyte ferroptosis plays an important role in prolonged I/R injury.